Pengaruh Harga dan Kualitas Produk Terhadap Kepuasan Konsumen di Fore Coffee Samarinda - Achmad Cheppy Baruna Mulki; Asnawati (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This research aim to determine the effect of price and product quality on consumer satisfaction at Fore Coffee Samarinda. The independent variables in this research are price and product quality, while the dependent variable is consumer satisfaction. The Population in this study were consumers at Fore Coffee Samarinda with sample determination using a non-probability sampling method with purposive sampling technique with a total of 110 respondents. This research is quantitative. Data analysis in this research uses the multiple linear regression analysis method using the IBM Statistical product and Service Solution (SPSS) Statistics version 25 program. The results of this research show that the influence of price and product quality has a positive and significant effect on consumer satisfaction at Fore Coffee Samarinda .